Sistemas agroflorestais como projetos de vida: um estudo a partir de um assentamento rural - Steyer, Fabia Schneider (2019)
Agroforestry Systens (SAFs) are a way of agricultural production in which the tree component is part of the agroecossystem. Due to advantageous characteristics of less use of external inputs, production diversity, low maintenance costs, among others, has been pointed out as an ideal strategy for rural development for family farming. In the Ipanema Settlement, located in Iperó / SP, several initiatives for the implementation of SAFs and environmental conservation occurred throughout its history. Between the years of 2013 to 2017 the projects Plantando Águas I and Projeto de Desenvolvimento Rural Sustentável Microbacias II – Acesso ao Mercado, implemented SAFs, and other actions, in this place. The objective of this research is to evaluate whether the SAFs implanted by these two projects contributed to the quality of life of settled families, and the relation with the permanence of the young people in the settlement. Data were collected through semi-structured interviews with key informants of the projects, with the families that were benefited and, through two focus groups, with some young people from these families. The speeches were used for analysis, through their content and discourse, also supported by observations noted in the field notebook. The results showed that the projects were means of accessing training and resources, and generated a positive impact on the lives of beneficiaries, adding 62 implanted areas. Technical Assistance and Rural Extension organizations and farmers (cooperatives and associations) also benefited from the physical structure and experience generated by the deployment process. However, some barriers were observed, the main discontinuity of projects and bureaucracy. Some of the barriers during the implementation process affected the full development of the SAF, and most are in the medium level of development. internal problems to the settlement and families also affected, such as lack of basic infrastructure, social vulnerability, low labor and access to markets, as well as limited financial resources for investment. Despite the difficulties, the SAF already show results as improved soil quality and increase food production, and most of the families have future projects linked to SAFs. As for the young people, the exodus of these to the city is recurrent, which is related mainly to poor infrastructure conditions and of difficulty of generating of own income of the young from the work in the lot. Still, many of these build life projects related to the settlement, even when not directly related to work in agriculture. The SAFs in the Ipanema Settlement are in a process of transition, and have brought expectations and encouragement to the community. The permanence, whether young people or other family members, are linked to socio-economic issues that go beyond the SAF, requiring that they are bound to a broader public policy development support. These experiences have generated benefits and learning, and, given the necessary stimulus, can be configured in an example of rural development around Agroecology and SAFs.